Explanation of the theory of âthe obligation of breastfeeding by mother and the necessity of paying its related costs by fatherâ from the perspective of Islamic jurisprudence - Ã™Â†Ã˜Â¸Ã˜Â±Ã›ÂŒ Ã˜ÂªÃ™ÂˆÃšÂ©Ã™Â„Ã›ÂŒ, Ã˜Â³Ã˜Â¹Ã›ÂŒÃ˜Â¯; ÃšÂ©Ã˜Â±Ã˜Â§ÃšÂ†Ã›ÂŒÃ˜Â§Ã™Â† Ã˜Â«Ã˜Â§Ã™Â†Ã›ÂŒ, Ã™ÂÃ˜Â§Ã˜Â·Ã™Â…Ã™Â‡ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
According to the prevailing view in the Islamic jurisprudence since breastfeeding is not mothers duty, she is entitled to demand wage from her husband for breastfeeding her child. In this article, the authors intend to prove, through reviewing the evidences of this view and the alternative one, that there is a meaningful relationship between the following phrases: âif they breastfeed for you, pay their wageâ and â their maintenance and clothing must be borne by fatherâ and that wage has no meaning other than meeting motherâs essential needs. This study has been performed in an analytical-descriptive method and the information was collected in library research method. After explaining the Quranology concepts and bases of the discussion, the Islamic jurisprudence texts will be analyzed and finally one of the raised views will be preferred over others. The conclusion is that breastfeeding is motherâs duty. During the marriage, mother is not permitted to demand wage from her husband in return of breastfeeding, unless the husband has consented to breastfeeding. After separation, mother is still obliged to breastfeed her child, but childâs father is bound to satisfy motherâs needs (food and clothing) in exchange for this service.